January effect: the existence in Malaysia stock market / Muhamad Faiz Irwan Fadzil - Fadzil, Muhamad Faiz Irwan (2013)
Past studies in the United States, Canada and Australia indicated the existence of seasonality effect, i.e. “January effect” due to taxes imposed on the capital gains in these countries. This paper attempted to find out whether or not this conclusion is also true in the case of Malaysia where there is no tax imposed on the capital gains. Initial observations showed that there is January effect in the year 2007. The mean daily return of January in year 2007 recorded the highest mean score compared to other months studied. Higher mean daily standard deviation in the month of January than other months somewhat reinforce the existence of January effects in the Malaysian market in the year 2007. However, the F-statistic indicated that the overall differences among these months were not statistically significant, which means there is no January effect or even seasonality effect in Malaysia